THE CULT[URE] OF THE CUSTOMER - Gay, Paul du; Salaman, Graeme (Journal of Management Studies, 1992)
ABSTRACTMuch organizational restructuring, at least in the UK and USA, seeks to replace organizational regulation by that of the market. These developments centre around an emphasis on relations with customers ‐ the ‘sovereign consumer’‐ as a paradigm for effective forms of organizational relations; they are apparent in, and underpin, a wide variety of organizational developments: just‐in‐time, total quality management, culture change programmes.Understanding these developments requires consideration of the discourse of enterprise of which the culture of the (internal) customer constitutes a key element. Defining internal organizational relations ‘as if’they were customer/supplier relations means replacing bureaucratic regulation and stability with the constant uncertainties of the market, and thus requiring enterprise from employees. This discourse has fundamental implications for management attempts to define working practices and relations and, ultimately, has impact on the conduct and identities of employees.Understanding these developments is not possible if analysis remains at the level of the organization. It requires that organizational restructurings, and the discourse which supports them, be located within the social and political rationality of enterprise. The certainties of management, the conviction that environmental challenge and competitive threat must be met by the cult[ure] of the customer, are due to managements’largely unquestioned acceptance of the normality and perceived good sense of the discourse of enterprise.